Morphological Investigation into Starch Bio-Nanocomposites via Synchrotron Radiation and Differential Scanning Calorimetry - Huihua Liu; Deeptangshu Chaudhary; Joseph John; Moses O. Tadé (Journal of Nanotechnology)
We studied a hydrophilic, plasticized bionanocomposite system involving sorbitol plasticizer, amylose biopolymer, and montmorillonite (MMT) for the presence of competitive interactions among them at different moisture content. Synchrotron analysis via small angle X-ray scattering (SAXS) and thermal analysis using differential scanning calorimetry (DSC) were performed to understand crystalline growth and the distribution of crystalline domains within the samples. The SAXS diffraction patterns showed reduced interhelix spacing in the amylose network indicating strong amylose-sorbitol interactions. Depending on the sorbitol and MMT concentration, these interactions also affected the free moisture content and crystalline domains. Domains of around 95 Å and 312 Å were found in the low-moisture-content samples as compared to a single domain of 95 Å in the high-moisture-content samples. DSC measurements confirmed that the MMT increased the onset and the melting temperature of nanocomposites. Moreover, the results showed that the ternary interactions among sorbitol-amylose-MMT supported the crystalline heterogeneity through secondary nucleation.